Weber-Christian panniculitis. Issue 4 (April 1987) - Conway, S P; Smithells, R W; Peters, W M
Abstract : Two cases of Weber-Christian panniculitis with onset at 7 months and 3 years 6 months are described. Both show evidence of disturbances in immune mechanisms. The family of the first case has a high prevalence of coeliac disease, and the mother of the first patient also suffers from alopecia areata and dermatitis herpetiformis.